Isolation, molecular typing and antimicrobial resistance of Clostridium difficile in dogs and cats in Lanzhou city of Northwest China - Wen, Gui-Lin; Li, Shi-Hong; Qin, Zhe; Yang, Ya-Jun; Bai, Li-Xia; Ge, Wen-Bo; Liu, Xi-Wang; Li, Jian-Yong (Frontiers in Veterinary Science, 2022)
Clostridium difficile infection (CDI) in human and animals belonged usually to antibiotic-associated diarrhea, ranging in severity from mild to life-threatening intestinal tract illnesses. This study aimed to isolation and characterization, toxin genes test, molecular typing, and drug sensitivity of Clostridium difficile (C. difficile) which were isolated from clinical diseased dogs and cats. A total of 247 clinical samples were collected from five animal hospitals in Lanzhou City of Northwest China, of which dogs and cats accounted for 74.9% (185/247) and 25.1% (62/247), respectively. We successfully identified 24 C. difficile strains by 16S rRNA and Matrix-Assisted Laser Desorption/Ionization Time of Fight Mass Spectroscopy (MALDI-TOF-MS). 10.3% (19/185) of dogs and 8.1% (5/62) of cats were positive for C. difficile. Among them, 16 strains were toxic and 8 were non-toxic, with a toxic rate of 57.9% (11/19) in dogs and 100% (5/5) in cats. A total of 10 STs and 10 RTs were identified in this study. The percentages of ST42 (RT106) and ST2 (RT014/LW01) among 16 toxic strains were 41.7% and 12.5%, respectively. However, ST3 (RT001), ST1 (RT027), ST133 (LW04), and ST-UN (LW04) had only one strain. ST42 (RT106) was the most common genotype and RT027 strain was first isolated in China from pets. Antimicrobial susceptibility test showed that isolates were extremely sensitive to vancomycin and metronidazole but were resistant to erythromycin and ciprofloxacin. The drug resistant rates to clindamycin, levofloxacin, moxifloxacin and meropenem were 62.5%, 20.8%, 16.7% and 8.3%, respectively. In conclusion, C. difficile was quietly prevalent in dogs and cats in Lanzhou city with RT106 and RT014 as the main ribotypes. The CDI in pets should be paying more attention and further studies are needed.